fMRI and corpus callosum relationships in monozygotic twins discordant for handedness. - Gurd, J; Cowell, P; Lux, S; Rezai, R; Cherkas, L; Ebers, G (2013)
To further investigate brain structure and function in 26 handedness discordant monozygotic twin pairs (MzHd), MRI and behavioural assessments were carried out. These showed significant correlation between language-specific functional laterality in inferior and middle frontal gyri, and anterior corpus callosum. Previous studies of handedness discordant monozygotic twins failed to resolve the issue concerning handedness and hemispheric laterality for language due to methodological disparities. The results would be relevant to genetic theories as well as to brain structure:function explanations. MzHd twins underwent MRI and fMRI scanning as well as behavioural assessment of motor performance and cognition. There were significant differences on MRI and fMRI laterality measures, as well as a significant correlation between anterior callosal widths and functional laterality. LH twins showed higher frequencies of atypical functional laterality. There was no significant within-twin pair correlation on fMRI verbal laterality, nor did results show within-twin pair differences on verbal fluency or IQ. Implications for the field of laterality research pertain to frontal hemispheric equipotentiality for verbal processes in healthy individuals. In particular, there can be an apparent lack of cognitive 'cost' to atypical laterality. An fMRI verbal laterality index correlated significantly with corpus callosum widths near Broca's area.